Competition of pathogens and probionts in cod yolk sac larvae measured in vivo, and the impact of increased temperature - Lillebø, Siril (The University of Bergen, 2011)
Aquaculture are today one of the biggest food-producing sectors in the world. Over the recent decades there has been a great increase in intensity and commercialization of aquaculture production, which has led to an unavoidable growth in disease problems. This has again led to a global over consumption of antibiotics and other pharmaceuticals which have caused problems as pollution, resistance and enormous losses for the industry. Farming of Atlantic cod, Gadus morhua, was anticipated to be the new success in Norwegian aquaculture after salmon, but partly due to the global financial crisis, and partly to high mortality - including the early life stages - the success have not become as large as expected. The high density of marine larvae and biological waste during rearing might contribute to high growth of opportunistic pathogenic bacteria, which could result in high larval mortality. Due to the fact that treatments with antibacterial agents are not favourable, and since vaccination is not possible due to the immature immune system of larvae, there has been carried out various studies to find new alternative treatments for the early life stages of cod and other marine species. The aim of this thesis is to enhance the knowledge of probiotics and test the possibility to use probiotics as an alternative for antibiotics in cod larval rearing facilities. In the present work a multi-dish system was used as a model for bath challenge experiment, and the species challenged with Vibrio anguillarum HI610 and different types of probiotics were cod egg/larvae. Cod eggs delivered from a commercial hatchery were randomly selected and placed separately in wells in a multi-dish system. Each well is seen as an independent unit and contained 2 ml of 80% aerated sterile seawater. After the eggs were placed in the wells, the wells were challenged with high dose (approximately 106 CFU ml-1) of different probiotic strains alone, and together with high dose (approximately 106 CFU ml-1) Vibrio anguillarum HI610. There were done ...